자궁경부편평상피암의 치료 전 SCC항원과 CYFRA 21-1의 측정치와 생존률간의 상관관계 - 변영지 (The Graduate School, Ajou University, 2005)
Objective: To determine the relationship between pretreatment serum squamous cell carcinoma (SCC) antigen and Cyfra 21-1 levels and survival in patients with invasive squamous cell carcinoma of the cervix. Method: 131 cervical squamous cell carcinoma patients were included. Pre-treatment levels of serum SCC antigen and Cyfra 21-1 were measured, with a 4 year minimum follow up. 32 recurrent disease (RD) patients were compared to 99 non-recurrent disease (NRD) paients with respect to tumor markers, FIGO stage, lesion size, lymph node status, and parametrial involvement. Statistical analysis of parameters was conducted for relationship with recurrent disease prediction and survival. Result: Pre-treatment serum SCC antigen and Cyfra 21-1 levels were significantly higher in the RD group ( p<0.001). Combiend serum SCC antigen and Cyfra 21-1 levels showed higher sensitivity for prediction of recurrence (90.6 %). Pre-treatment SCC antigen and Cyfra 21-1 levels showed significant correlation with high FIGO stage, large lesion size, lymph node status and parametrial involvement (p<0.001). Normal pre-treatment levels of SCC antigen and Cyfra 21-1 showed a 5-year survival rate of 93 % and 90 % respectively, while elevated levels showed significantly decreased survival rate of 63% and 59%, respectively ( p<0.001). Odd ratio for cumulative survival rate were 6.87 for SCC antigen, and 5.07 for Cyfra 21-1 (p<0.001). Conclusion: Initial pre-treatment levels of serum SCC antigen and Cyfra 21-1 are closely related to FIGO stage, lesion size, lymph node and parametrial involvement in patients with squamous cell carcinoma of the cervix. Also, these markers may be of help to predicting recurrent disease and survival rate.
학위논문(석사)--아주대학교 대학원 :의학과,2005. 8
Keywords: 자궁경부 편평상피암; SCC 항원; Cyfra 21-1; 생존률